(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The present study reviews environment-related articles in official newsletters issued by municipalities in Latvia. It evaluates the themes and contents associated with environment in order to evaluate the performance of newsletters as providers of relevant information to the population. Official publications of four Latvian municipalities—Mazsalaca, Jūrmala, Krāslava, and Kandava—were analyzed. Common themes included nature and its protection, history of the place, social and cultural events, quality of life and performance of the municipality. A widespread approach of engaging the local population is to hold contests and competitions. However, it is uncertain if the response rate help raising the civic participation level significantly. The official newsletters are willing to publish environment-related public relations materials prepared by other institutions of companies, without exhibiting consistent editorial policy of their own. The implications of the continued publication of these newsletters as competitors to the regional independent newspapers are also discussed.